Sagot :
factoring: x^2-x-6=0
(x-3)(x+2)=0
completing: (x^2+x+1/4)+6+1/4
√ x+1/2=√25/4
x+1/2=+-5/2
x=-1+5/2=4/2 or 2
x=-1-5/2=-6/2 or -3
(x-3)(x+2)=0
completing: (x^2+x+1/4)+6+1/4
√ x+1/2=√25/4
x+1/2=+-5/2
x=-1+5/2=4/2 or 2
x=-1-5/2=-6/2 or -3
For quadratic formula, substitute the values of a = 1; b=-1 and c = 6 to quadratic formula, you can do it.
COMPLETING THE SQUARE: ax² + bx + (b/2)² = c + (b/2)²
x² - x - 6 = 0
x² - x + (1/2)² = 6 + (1/2)²
x² - x + 1/4 = 6 + 1/4 (LCD is 4)
(x-1/2)² = (24+1)/4
[tex] \sqrt{( x^{2} - 1/2) ^{2} } = \sqrt{ \frac{25}{4} } [/tex]
x-1/2 = + or - 5/2
x = 5/2 + 1/2
x = 6/2
x = 3
x = -5/2 + 1/2
x = -4/2
x = -2
FACTORING:
x² - x -6 = 0
Factor: (x - 3) (x + 2) = 0
x-3 = 0
x = 3
x+ 2 = 0
x = -2
x = 3 ; x = -2
COMPLETING THE SQUARE: ax² + bx + (b/2)² = c + (b/2)²
x² - x - 6 = 0
x² - x + (1/2)² = 6 + (1/2)²
x² - x + 1/4 = 6 + 1/4 (LCD is 4)
(x-1/2)² = (24+1)/4
[tex] \sqrt{( x^{2} - 1/2) ^{2} } = \sqrt{ \frac{25}{4} } [/tex]
x-1/2 = + or - 5/2
x = 5/2 + 1/2
x = 6/2
x = 3
x = -5/2 + 1/2
x = -4/2
x = -2
FACTORING:
x² - x -6 = 0
Factor: (x - 3) (x + 2) = 0
x-3 = 0
x = 3
x+ 2 = 0
x = -2
x = 3 ; x = -2